Study the effects of calcinations and evolution of crystallographic parameters of two Tunisian natural phosphates - Chaabouni, Ahmed; Chtara, Chaker; Nzihou, Ange; El Feki, Hafed (International Journal of Advanced Chemistry, 2014)
Tunisian natural phosphate is a highly form of fluorapatite, carbonate fluorapatite, also known as “francolite”. The presence of carbonate in mineral phosphates influences their reactivity overlooked acid attack, but their presence requires a supplementary adding of sulfuric acid in the plants of production of phosphoric acid; and causing the formation of foams in the reactors during the addition of sulfuric acid. The presence of carbonates in high contents reduces the price value of phosphate rock. We propose in this work to study thermally the decomposition of two carbonated fluorapatite in a range of temperature between ambient and 1000°C; and the variation of the value of crystallographic parameters of the two samples of phosphate. The X-ray diffraction technique is used for this mineralogical study. By referring to the crystallographic parameters of the lattice of phosphate, we note that the increase in temperature decarbonated the francolite which is transformed largely to a fluoroapatite. In addition, it was reported that the first decarbonation is around 650°C translated the kinetics of decomposition of the carbonate ions of the type B associated with a vaccum, while the second decarbonation is around 1000°C and related to the thermal decomposition of the entity of CO3F, generated by the decomposition of carbonate ions of type B and A. The presence of these ions would be the result of a reorganization of the crystal lattice. Keywords: Carbonated fluoroapatite, effect of calcinations, mineralogical study, Tunisian natural phosphate, x-ray diffraction.